AN ANALYSIS OF SPEECH FUNCTION AT TRADITIONAL SHOPPING CENTER IN LANGSA - Isda, Irma Dewi (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2019)
This study deals with Speech function at traditional shopping center in Langsa. The objectives of this study are to find out the types of speech function, the most dominant type of speech function used, and the meaning of the dominantly used. The research of this study was carried by using descriptive qualitative. The data were taken from ten sales and buyers conversation using longer and short conversation at traditional shopping center. The data were analyzed and classified into four types of speech functions namely statement, question, offer, and command. The findings indicated based on longer and short conversation there are statement 43 (40,18%), question 53(49,53%), offer 7 (6,5%), command 4 (3,73%) while on short conversation are statement 13 (30.9%), Question 22 (52,3%), offer 5(11,9%) and Command 2(4,7%). Question as the most dominant type of speech function used in sales and buyers on both conversation. It means questions always happened in the traditional shopping center to give demand and information.